Characterization of the Zebu cattle population with a certificate of genealogical registration in Costa Rica - Vásquez-Loaiza, Marilyn (2020)
Introduction. There is not much information on pure cattle with a genealogical certificate in Costa Rica. It is necessary to know the status of this population to direct efforts towards the productive improvement of the Zebu cattle breeds. Objective. To update the database of the Costa Rican Cebu Cattle Breeders Association (ASOCEBÚ), characterize this population and analyze the use of males of the gray Brahman breed in the country. Materials and methods. An inventory was done in 121 herds to update the Association’s database to 2018. The information was sorted by breed, sex, age, total animals, breeders, socio-economic region, province, and canton. The frequency of use of gray Brahman breeders was determined. Results. A total of 10 995 pure animals were counted, distributed in six breeds (gray Brahman, red Brahman, Nelore, Gyr, Guzerat, and Indubrasil). The gray Brahman breed predominated with 74.5 % of the population and 76.8 % of the total of breeders. The Chorotega region had the highest registered population (49.5 %) and the highest number of breeders (37.2 %). 55.8 % of the total population came from ten breeders, however, the largest number of herds corresponds to farms with few animals. In the gray Brahman breed, 60.8 % of the population comes from domestic bulls, and 39.2 % from other countries. Conclusion. Registered pure zebu cattle are distributed throughout the whole country. Attention should be put to genetic management to minimize inbreeding. Census and survey managers are encouraged to include the purebred populations in their assessments.